Solve for x:x/5 - 2 = x/2 + 3
Put each term in x/5 - 2 over the common denominator 5: x/5 - 2 = x/5 - (10)/5:x/5 - (10)/5 = x/2 + 3
x/5 - (10)/5 = (x - 10)/5:(x - 10)/5 = x/2 + 3
Put each term in x/2 + 3 over the common denominator 2: x/2 + 3 = x/2 + 6/2:(x - 10)/5 = x/2 + 6/2
x/2 + 6/2 = (x + 6)/2:(x - 10)/5 = (x + 6)/2
Multiply both sides by 10:(10 (x - 10))/5 = (10 (x + 6))/2
10/5 = (5×2)/5 = 2:2 (x - 10) = (10 (x + 6))/2
10/2 = (2×5)/2 = 5:2 (x - 10) = 5 (x + 6)
Expand out terms of the left hand side:2 x - 20 = 5 (x + 6)
Expand out terms of the right hand side:2 x - 20 = 5 x + 30
Subtract 5 x from both sides:(2 x - 5 x) - 20 = (5 x - 5 x) + 30
2 x - 5 x = -3 x:-3 x - 20 = (5 x - 5 x) + 30
5 x - 5 x = 0:-3 x - 20 = 30
Add 20 to both sides:(20 - 20) - 3 x = 20 + 30
20 - 20 = 0:-3 x = 30 + 20
30 + 20 = 50:-3 x = 50
Divide both sides of -3 x = 50 by -3:(-3 x)/(-3) = 50/(-3)
(-3)/(-3) = 1:x = 50/(-3)
Multiply numerator and denominator of 50/(-3) by -1:Answer: x = (-50)/3
Answer:
It can't be a kite. A kite has 2 pairs of equal sides.
Step-by-step explanation:
Length =l
Height = h
Area function = l * h = 924
Perimeter function = 2i + 2h = 122
Divide by 2
I + h = 61.
Plug in I or h for the other variable
I * (61 - I) = 924
61i - i^2 = 924
Factor the function
(-I + 28)(I - 33) = 0
l = 33 as l cannot be negative
61 - 33 = 28
h = 28
Difference between h and l is 33-28=5
Answer:
His error is adding 10 and 2/3 before multiplying by a(age of the tree)
Step-by-step explanation:
The sum of 10 and two-thirds of that tree's age, in years, is equal to 50.
Correct equation
Sum = addition (+)
two-thirds = 2/3
The tree's age = a
10 + 2/3a = 50
2/3a = 50 - 10
2/3a = 40
a = 40 ÷ 2/3
= 40 × 3/2
= 60
a = 60 years
Javier writes the equation
(10 + two-thirds) a = 50
(10 + 2/3)a = 50
(30+2/3)a = 50
32/3a = 50
a = 50 ÷ 32/3
= 50 × 3/32
= 150/32
a = 150/32
His error is adding 10 and 2/3 before multiplying by a(age of the tree)
Answer:
what i did was multiply 33*6 and got 198 and then 228-198 to find out that the initial fee was 30 dollars. then multiply 33*9+30 to get a 9-month total cost of $327
Step-by-step explanation:
cost = $33 per month + fee
1. c(m) = 33m + f
33(6) + f = 228
198 + f = 228
f = $30 membership fee
c(m) = 33m + 30
2. at 9 months: 33(9) + 30 = $327
hopefully this helps :)
have a nice day !!